The Intermediate School Mathematics Teachers' Role in creating Professional Standards- based Learning Environments of The Education and Training Evaluation Commission from the Specialists' Perspectives - Al- Maliki, Ahmed Suleiman Yahya (Journal of Educational and Psychological Sciences, 2022)
This research aims to identify the role of middle school mathematics teachers in creating interactive learning environments based on the professional standards of the Learning and Training Evaluation Authority from the specialists' point of view. To achieve this, the researcher used the descriptive method with its survey design. The research sample included (120) individuals, (5) teaching Staff Members of curricula and mathematics, and (19) educational supervisors in the mathematics department in Makkah Directorate of education. The role of the middle school mathematics teacher in creating interactive learning environments based on the professional standards of the Education and Training Evaluation Authority from the point of view of specialists came with a degree of (approval). The arrangement of the axes was descending as follows: (the use of modern technology in teaching mathematics, strategies for teaching mathematics, the time teaching mathematics effectively, the use of mathematical communication) for all axes (4,24,4,47,4,47,4,50). There is statistically significant difference at the level of significance (0.05) between the averages of the specialists' responses according to the job title (teacher, educational supervisor, faculty member) due to the effective use of modern technology for mathematics and teaching mathematics effectively, and it reached (5,275,5,93). There is statistically significant difference at the level of significance (0.05) between the averages of the specialists' responses according to the job title (teacher, educational supervisor, faculty member) due to the use of mathematics teaching strategies and using the mathematical communications, and it reached (6,749,7,434). There is a statistically significant difference at the level of significance (0.05) between the averages of the specialists' responses according to the academic qualification (BA, MA, and PhD). There is a statistically significant difference at the level of (0.05) between averages of responses attributed to years of experience, at the role of mathematics teacher in using modern technology and strategies for teaching mathematics, the time of effectively teaching mathematics, mathematical communication reached (13,863,17,806,14,356,9,548). The researcher recommended a number of recommendations, including strengthening professional practices related to creating interactive learning environments and providing educational supervisors with the proposed vision that came out of this study in promoting an interactive educational environment.
Keywords: mathematics teachers; mathematics; practices for creating interactive learning environments